2020
DOI: 10.15252/msb.20198985
|View full text |Cite
|
Sign up to set email alerts
|

Bile canaliculi remodeling activates YAP via the actin cytoskeleton during liver regeneration

Abstract: The mechanisms of organ size control remain poorly understood. A key question is how cells collectively sense the overall status of a tissue. We addressed this problem focusing on mouse liver regeneration. Using digital tissue reconstruction and quantitative image analysis, we found that the apical surface of hepatocytes forming the bile canalicular network expands concomitant with an increase in F‐actin and phospho‐myosin, to compensate an overload of bile acids. These changes are sensed by the Hippo transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 62 publications
(156 reference statements)
5
43
0
Order By: Relevance
“…Cell density was measured by counting the number of nuclei (DAPI) covering an area of 547.95 µm × 365.3 µm. Finally, localization of nuclear YAP protein was calculated by measuring fluorescence intensity, using the corrected total cell fluorescence [CTCF = Integrated Density − (Area of selected cell × Mean fluorescence of background readings] [ 40 ] in the area merged by DAPI.…”
Section: Methodsmentioning
confidence: 99%
“…Cell density was measured by counting the number of nuclei (DAPI) covering an area of 547.95 µm × 365.3 µm. Finally, localization of nuclear YAP protein was calculated by measuring fluorescence intensity, using the corrected total cell fluorescence [CTCF = Integrated Density − (Area of selected cell × Mean fluorescence of background readings] [ 40 ] in the area merged by DAPI.…”
Section: Methodsmentioning
confidence: 99%
“…The position of the bulkheads could be determined by mechano-sensing mechanisms coupled to the tension and local curvature through the actin cortical mesh (Meyer et al, 2020). The bulkheads were detected in the embryonic liver, suggesting that they are not a cell culture artefact but have physiological relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, work from Skouloudaki et al, Xu et al, and Meyer et al showed that Yki in the Drosophila trachea/wing disc and YAP in murine hepatocytes are enriched in the apical F-actin area, where they interact with actin cytoskeleton molecules to regulate tissue morphogenesis [ 14 , 18 , 19 ]. More specifically, these groups found that Yki and YAP interact with actin cytoskeletal components, such as Twinstar (Tsr), Trio, Dia, and Cingulin.…”
Section: Apical Cell Cortex: a Site Of Yap/yki And Actin Cytoskelementioning
confidence: 99%
“…On the other hand, Meyer et al found that during liver resection, the apical membrane of hepatocytes expanded and actomyosin contractility increased. These changes are “sensed” by YAP, which is recruited to the apical cortex of hepatocytes and translocates in the nucleus [ 14 ]. YAP nuclear translocation can be modified by perturbations of the actin cytoskeleton and pMLC levels.…”
Section: Apical Cell Cortex: a Site Of Yap/yki And Actin Cytoskelementioning
confidence: 99%
See 1 more Smart Citation